Pemikiran Hukum Ibnu Hazm - Yasin, Noer (UIN Maulana Malik Ibrahim Malang, 2005)
The works of Ibnu Hazm, i.e. al Muhalla bi al Atsar, an encyclopedia of fiqh of mazhab zhahiri which is also a result of ‘istinbath’ and ‘ijtihad’ of Ibnu Hazm in Fiqh, becomes the most substantial reference because of the scarcity of written source of mazhab zhahiri. Another important work of his is al Ihkam fi Ushul al Ahkam becomes the only primary source of ijtihad method of the same mazhab. The birth of the greatest works gives the influential position for Ibnu Hazm and his works in this mazhab. Talking about mazhab zhahiri’s position and role in its development, he is well known as the most prominent figure after Daud al Ashbihani. Even, he is more radical compared to his ancestors and is called as the founder of two mazhab, Muhammad Abu Zahrah, Muhadharat fi Tarikh al Mazahib, al Fiqhiyyat. Karya Ibnu Hazm seperti al Muhalla bi al Atsar, sebuah ensiklopedi fikih mazhab zhahiri yang sekaligus merupakan hasil istinbath dan ijtihad Ibnu Hazm di bidang Fikih, menjadi buku referensi terpenting di tengah kelangkaan sumber tertulis tentang mazhab zhahiri. Demikian pula karyanya al Ihkam fi Ushul al Ahkam menjadi satu-satunya sumber primer metode ijtihad karya ulama mazhab ini. Munculnya karya-karya besar ini telah menempatkan Ibnu Hazm dan karya-karyanya pada mazhab ini. Tak heran jika kedudukan dan peranan yang amat penting dalam sejarah dan perkembangan mazhab ini, ia dikenal sebagai tokoh yang paling menonjol dalam mazhab zhahiri setelah Daud al Ashbihani. Bahkan ia lebih radikal disbanding pendahulunya itu dan disebut sebagai pendiri kedua mazhab ini, Muhammad Abu Zahrah, Muhadharat fi Tarikh al Mazahib, al Fiqhiyyat.